2003
DOI: 10.1115/1.1577356
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Shape Similarity Assessment Algorithms for Product Design and Manufacturing Applications

Abstract: Shape similarity assessment is a fundamental geometric reasoning problem that finds application in several different product design and manufacturing applications. A computationally efficient way to assess shape similarity is to first abstract 3D object shapes into shape signatures and use shape signatures to perform similarity assessment. Several different types of shape signatures have been developed in the past. This paper provides a survey of existing algorithms for computing and comparing shape signatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(94 citation statements)
references
References 48 publications
0
90
0
Order By: Relevance
“…Funkhouser et al [9] partially matched shape features according to different priorities. More extensive surveys and literature reviews in this area can be found in references [5], [18], and [29].…”
Section: Comparing Shape Models Of Cadmentioning
confidence: 99%
“…Funkhouser et al [9] partially matched shape features according to different priorities. More extensive surveys and literature reviews in this area can be found in references [5], [18], and [29].…”
Section: Comparing Shape Models Of Cadmentioning
confidence: 99%
“…Various shape matching methods exist (Tangelder and Veltkamp, 2008;Cardone et al, 2003;Iyer et al, 2005;Li et al, 2010;Brière-Côté et al, 2012;Demirci et al, 2008;Zhu et al, 2012;Ohbuchi et al, 2005) and can be classified in three main categories: feature-based methods, graph-based methods and geometry-based methods (Figure 2). These methods have been implemented and tested and the results are more or less efficient but only when trying to retrieve a shape which is similar to the one of the query from the point of view of form and structure.…”
Section: Related Workmentioning
confidence: 99%
“…In the first substep, the closest neighbors for each FAAV pi ∈ P need to be obtained by using the distance function defined in Equation (2). The distance function accounts for the relevant FAAV attributes.…”
Section: Building the Set Of Theta Intervals For The Faavs Of Set Pmentioning
confidence: 99%
“…We have presented a survey in [2]. Representative techniques include shape histogram-based techniques [9,13,18,21], graph-based techniques [1,10,19], spatial function based techniques [5,6,11,16,17], feature-based techniques [2,3,8,14,22]. The features can be represented as points or vectors in n dimension space where each dimension represents some significant characteristic of the feature.…”
mentioning
confidence: 99%